Constraining High-energy Neutrino Emission from Supernovae with IceCube - R. Abbasi; M. Ackermann; J. Adams; S. K. Agarwalla; J. A. Aguilar; M. Ahlers; J. M. Alameddine; N. M. Amin; K. Andeen; G. Anton; C. Argüelles; Y. Ashida; et al. (The Astrophysical Journal Letters, 2023)
Core-collapse supernovae are a promising potential high-energy neutrino source class. We test for correlation between seven years of IceCube neutrino data and a catalog containing more than 1000 core-collapse supernovae of types IIn and IIP and a sample of stripped-envelope supernovae. We search both for neutrino emission from individual supernovae as well as for combined emission from the whole supernova sample, through a stacking analysis. No significant spatial or temporal correlation of neutrinos with the cataloged supernovae was found. All scenarios were tested against the background expectation and together yield an overall p -value of 93%; therefore, they show consistency with the background only. The derived upper limits on the total energy emitted in neutrinos are 1.7 × 10 ^48 erg for stripped-envelope supernovae, 2.8 × 10 ^48 erg for type IIP, and 1.3 × 10 ^49 erg for type IIn SNe, the latter disfavoring models with optimistic assumptions for neutrino production in interacting supernovae. We conclude that stripped-envelope supernovae and supernovae of type IIn do not contribute more than 14.6% and 33.9%, respectively, to the diffuse neutrino flux in the energy range of about [ 10 ^3 –10 ^5 ] GeV, assuming that the neutrino energy spectrum follows a power-law with an index of −2.5. Under the same assumption, we can only constrain the contribution of type IIP SNe to no more than 59.9%. Thus, core-collapse supernovae of types IIn and stripped-envelope supernovae can both be ruled out as the dominant source of the diffuse neutrino flux under the given assumptions.